2011
DOI: 10.1080/09500340.2011.564317
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries in peripheral ocular aberrations

Abstract: A mirror symmetry in the aberrations between the left and right eyes has previously been found foveally, but while a similar symmetry for the peripheral visual field is likely, it has not been investigated. Nevertheless, the peripheral optical quality is often evaluated in only one eye, because it is more time efficient than analyzing the whole visual field of both eyes. This study investigates the correctness of such an approach by measuring the peripheral wavefront aberrations in both eyes of 22 subjects out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…A high degree of interocular symmetry also exists for the total higher-order aberrations of the eye after correcting for enantiomorphism (between eye mirror symmetry) in various isometropic populations during distance [171][172][173][174][175] and near fixation. 176 Studies of chicks 177,178 have reported a significant increase in higher-order aberrations following monocular form deprivation and the development of myopia, and recently Colletta, Marcos and Troilo 179 observed that experimentally form-deprived eyes of marmosets had significantly higher levels of the asymmetric aberration trefoil compared to the fellow control eye. These animal models suggest that interocular asymmetries in higher-order aberrations may be a result of asymmetric visual experience and/or ocular growth, rather than a cause.…”
Section: Total Ocular Higherorder Aberrationsmentioning
confidence: 99%
“…A high degree of interocular symmetry also exists for the total higher-order aberrations of the eye after correcting for enantiomorphism (between eye mirror symmetry) in various isometropic populations during distance [171][172][173][174][175] and near fixation. 176 Studies of chicks 177,178 have reported a significant increase in higher-order aberrations following monocular form deprivation and the development of myopia, and recently Colletta, Marcos and Troilo 179 observed that experimentally form-deprived eyes of marmosets had significantly higher levels of the asymmetric aberration trefoil compared to the fellow control eye. These animal models suggest that interocular asymmetries in higher-order aberrations may be a result of asymmetric visual experience and/or ocular growth, rather than a cause.…”
Section: Total Ocular Higherorder Aberrationsmentioning
confidence: 99%
“…8,11,15,35 The aberration coefficients with negative, even m indices or positive, odd m indices had negative fellow eye correlations across the visual field because the coefficients had opposite signs at corresponding temporal or nasal visual field locations of fellow eyes. Supporting previous studies for aberrations at fixation or along the horizontal meridian of the visual field, 14,[16][17][18][19][20][21][22][23][24][25][26][27][28]32 in a pooled data set the sign of these coefficients should be altered for left eye data. 36 Mirror symmetry was found between fellow eyes across the visual field for most peripheral aberration coefficients.…”
Section: Discussionmentioning
confidence: 97%
“…A requirement for mirror symmetry between eyes is an absolute slope of 1.0. Across all visual field angles and participants, absolute slopes of 0.90 to 1.10 occurred in regressions for all second-order terms (C 16 and for C , 32 indicating mirror symmetry for these coefficients, although the significances were not tested. The studies did not mention whether any of the participants had anisometropia.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations